(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Sharp breath of the roads infections whole world along children’s illness and death main from the reasons one to be global on a scale respirator infections from 0 to 5 years old was 2 million children close to death reason to be guess Approximately 80% of these respiratory infection cases are caused by viral pathogens such as influenza A and B, respiratory syncytial virus A and B, parainfluenza virus types 1-3, adenovirus, rhinovirus, human metapneumovirus, and others.